Editorial Perspective: Prioritizing child and adolescent mental health research in the context of war - Zhang, Alexa X.D.; Osokina, Olga; Silwal, Sanju; Skokauskas, Norbert; Sourander, Andre; Hodes, Matthew (Wiley, 2026)
Given the high level of exposure of children and adolescents (CA) to war and associated adversities (1 in 6 children live in war zones at the time of writing) and very detrimental effects on their mental health, we argue for the need to involve them in mental health research. Although there is abundant literature on CA mental health research in nonwar and postwar settings, the findings cannot be directly extrapolated to war contexts. Viewing CA as too vulnerable, as well as ethical and methodological challenges are among the reasons for the low level of research on this topic. Drawing on the available literature and our experience conducting epidemiological studies on the impact of the war following the Russian invasion of Ukraine, we highlight the complexity and importance of conducting CA mental health research during wars and the key ethical and methodological considerations. We advocate the active inclusion of CA as research participants and beneficiaries as a first step to building an evidence base for treatment and services.